Стилі навчання у контексті дистанційної освіти - Симоненко, Світлана Вікторівна; Симоненко, Светлана Викторовна; Symonenko, Svitlana (ТДАТУ, 2021)
The article deals with the issue of learning styles within the context of distance education. It is stated that determination of learning styles is useful for all agents of the educational process, since it can help teachers choose appropriate teaching methods for students with different learning styles. Certain recommendations for distant course components are given.
Keywords: learning styles; distance education; online learning; online course; higher educational institutions